Studies on the Homalomeneae (Araceae) of Borneo XXVI—A new and highly ornamental species of Homalomena [Punctulata Clade] from Triassic-Jurassic karst formations in SW Sarawak - Wong, Sin Yeng; Boyce, Peter C. (Magnolia Press, 2020)
Homalomena benedikii is described and illustrated as a new species from Serian Division, SW Sarawak, where it is restricted to forested Triassic-Jurassic karst formations, and compared with the two most similar described species H. cowleyae and H. imitator, from shales in NE Sarawak and Brunei, and C Sarawak, respectively.